Metal-based flexible copper clad laminate and method of manufacturing the same

CN122976133APending Publication Date: 2026-10-27ZHUHAI HONGYI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611259855.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]现有传统PI基FCCL材料在5GHz以上超高频、毫米波频段应用中,存在四大无法规避的行业瓶颈,已不能满足下一代高频高速信号传输需求:

Benefits of technology

[0030]1、本发明绝缘胶膜采用无极性脂肪族碳氢树脂体系,不含PI极性材料,配合梯度预烘、高温交联、长时间真空脱挥工艺彻底去除小分子杂质,成品在5GHz~100GHz频段Dk≤2.5、Df≤0.001,毫米波信号衰减大幅降低,适配各类高频射频器件,实现了超低高频传输损耗,同时中心铜基板与外层导电铜箔均为铜质,二者热膨胀系数完全一致,压合、回流焊、高低温循环后不会发生板材翘曲、线路偏移、阻抗漂移,长期高低温循环尺寸漂移量≤0.1%,线路加工精度显著提升,彻底消除层间热应力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976133A_ABST
    Figure CN122976133A_ABST
Patent Text Reader

Abstract

The application discloses a metal-based flexible copper-clad foil and a preparation method thereof. The metal-based flexible copper-clad foil comprises a copper substrate, insulating adhesive films are attached to the top and bottom of the copper substrate, and conductive copper foils are attached to the sides of the insulating adhesive films away from the copper substrate. The insulating adhesive films adopt a non-polar aliphatic hydrocarbon resin system and do not contain PI polar materials. Small molecular impurities are completely removed through a gradient pre-baking, high-temperature cross-linking and long-time vacuum devolatilization process. The finished product has a Dk≤2.5 and a Df≤0.001 in a 5GHz-100GHz frequency band, the millimeter wave signal attenuation is greatly reduced, the metal-based flexible copper-clad foil is suitable for various high-frequency radio frequency devices, and the ultra-low high-frequency transmission loss is realized. Meanwhile, the central copper substrate and the outer conductive copper foil are both made of copper, the thermal expansion coefficients of the two are completely consistent, and the copper-clad foil will not be warped, the circuit will not be deviated, and the impedance will not be drifted after being pressed, reflow soldered and subjected to high-low temperature cycles. The long-term high-low temperature cycle size drift is less than or equal to 0.1%, the circuit processing precision is significantly improved, and the interlayer thermal stress is completely eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of manufacturing high-frequency, high-speed flexible printed circuit boards and radio frequency antennas, specifically to a metal-based flexible copper-clad foil and its preparation method. Background Technology

[0002] With the rapid iteration of artificial intelligence, high-speed communication, autonomous driving, and millimeter-wave radar technologies, electronic devices are developing rapidly towards higher frequencies, higher speeds, lighter weights, greater flexibility, and lower signal loss. High-frequency, high-speed flexible printed circuits (FPCs), as core components in AI terminals, high-speed servers, millimeter-wave antennas, and automotive radar, place extremely stringent technical requirements on the dielectric properties, dimensional stability, internal stress, shielding performance, and resistance to high and low temperature cycling of the substrate.

[0003] Currently, the industry-standard high-frequency flexible substrate is the traditional FCCL flexible copper-clad laminate structure, which typically consists of: (PI) film + adhesive layer + copper foil, or copper foil + adhesive layer + PI film + adhesive + copper foil. Polyimide film serves as the insulating support substrate, and copper foil serves as the conductive circuit layer.

[0004] Existing traditional PI-based FCCL materials face four unavoidable industry bottlenecks in ultra-high frequency and millimeter-wave applications above 5GHz, and can no longer meet the requirements of next-generation high-frequency and high-speed signal transmission:

[0005] Poor dielectric properties and high high-frequency signal loss: Polyimide (PI) resin molecules are highly polar, have a high dielectric constant Dk, and a large dielectric loss tangent Df. At frequencies above 5 GHz, especially in the tens to 10 GHz millimeter wave band, signal polarization loss and relaxation loss are amplified sharply, resulting in severe signal attenuation, low transmission efficiency, and large phase shift. This makes it completely unacceptable for the transmission requirements of ultra-high-speed millimeter wave antennas above 50 GHz.

[0006] Mismatched coefficients of thermal expansion and extremely high internal stress: In traditional structures, the coefficients of thermal expansion of the PI insulating film and the copper foil differ significantly. During the FPC manufacturing process, such as lamination, etching, reflow soldering, and high and low temperature cycling, huge residual internal stress is generated between the layers, resulting in warping, dimensional deviation, circuit deviation, impedance instability, and poor high-frequency consistency of the finished product, which seriously affects the radiation performance of the millimeter-wave antenna and the high-frequency impedance accuracy of the circuit.

[0007] Poor dimensional stability and low high-frequency consistency: Ordinary organic thin film substrates have large temperature deformation. Under long-term temperature fluctuations in high-frequency and high-speed circuits, the dielectric thickness and Dk / Df parameters drift significantly, resulting in RF antenna gain fluctuations, deterioration of VSWR, and poor circuit signal consistency, making them unsuitable for high-end millimeter-wave precision devices.

[0008] Lacking native shielding capability and high cost: Traditional PI-based FCCLs lack a metal substrate shielding structure, making them prone to crosstalk and electromagnetic interference in high-frequency circuits; at the same time, high-end high-frequency PI films rely on imports, have high raw material costs, and are subject to supply chain constraints, resulting in high mass production costs.

[0009] In summary, traditional PI-based flexible copper-clad laminate structures are no longer suitable for the high-end application requirements of 5G / 6G ultra-high frequency high-speed circuits, 77GHz millimeter-wave radar, and flexible RF antennas. The industry urgently needs a new type of flexible high-frequency substrate with low dielectric constant, low loss, zero thermal expansion matching stress, self-shielding, low cost, and high stability. Summary of the Invention

[0010] The purpose of this invention is to provide a metal-based flexible copper-clad foil and its preparation method, so as to solve the problems mentioned in the background art.

[0011] To achieve the above objectives, the present invention provides the following technical solution: a metal-based flexible copper-clad foil, comprising a copper substrate, wherein an insulating film is attached to both the top and bottom of the copper substrate, and a conductive copper foil is attached to the side of the insulating film away from the copper substrate, wherein both the copper substrate and the conductive copper foil are made of copper and have the same coefficient of thermal expansion, and the copper substrate forms a full-area electromagnetic shielding structure.

[0012] The insulating film is composed of a nonpolar aliphatic hydrocarbon resin system, with an internal three-dimensional network cross-linked structure. By mass, the insulating film is made of 100 parts aliphatic hydrocarbon resin, 0.1-20 parts peroxide and 3-50 parts polyvinyl cross-linking agent. The aliphatic hydrocarbon resin has a nonpolar pure hydrocarbon molecular structure.

[0013] Optionally, in the 5GHz-100GHz frequency band, the dielectric constant Dk of the insulating film is ≤2.5 and the dielectric loss Df is ≤0.001.

[0014] A method for preparing a metal-based flexible copper-clad laminate, the method comprising the following steps:

[0015] S1 Raw Material Pretreatment and Mixing: Weigh 100 parts aliphatic hydrocarbon resin, 0.1-20 parts peroxide and 3-50 parts polyvinyl crosslinking agent according to the mass ratio. First, put the solid resin into the mixing tank and pre-stir at room temperature for 5 minutes to break up the lumps. Then, add the crosslinking agent in sequence. The stirring speed is stably controlled at 300-800 r / min. Stir continuously for 20-60 minutes. The stirring process is completely sealed and protected from light. After stirring, let it stand for 10-30 minutes to remove bubbles and obtain a homogeneous coating raw material without particles.

[0016] S2 Coating Film Forming: Mirror release PET is selected as the carrier substrate. The degassed coating material is evenly coated on the surface of the release film using a slit coater. The wet film thickness is controlled at 30-120μm. The coating environment is kept at a constant temperature of 25℃ and humidity of 40%-60% to avoid rapid evaporation of the wet film and the generation of pinholes and shrinkage defects.

[0017] S3 Segmented Gradient Pre-drying: The release film carrying the wet adhesive film is sent into a segmented hot air oven and dried in two sections with controlled temperature. The temperature of the first oven is 140℃ and held for 10-25 minutes. Low-speed hot air slowly evaporates the low-boiling-point solvent. The temperature of the second oven is raised to 150℃ and held for 15-30 minutes to further remove residual solvent. The hot air velocity in both ovens is controlled at 0.8-1.5m / s to prevent the film surface from drying and the internal solvent from being trapped and bubbling.

[0018] S4 Constant Temperature Deep Crosslinking: The pre-baked film, along with the release film, is transferred into a sealed curing oven. The entire oven is heated to 170℃ and kept at that temperature for 40-90 minutes. Hot air is circulated inside the oven to fully decompose the peroxides and initiate an addition crosslinking reaction between the resin and the polyvinyl crosslinking agent, forming a complete continuous three-dimensional network molecular structure. This ensures a crosslinking reaction conversion rate of ≥95%.

[0019] S5 High Temperature Vacuum Deep Deviation: After cross-linking, the release film is peeled off and placed in a vacuum oven. The oven temperature is kept constant at 180-200℃, and the internal vacuum degree is maintained at ≤0.01MPa. Deviation treatment is carried out for 2-5 hours. During the process, the vacuum is broken and the air is replaced every 30 minutes to fully extract unreacted monomers, small molecule by-products and residual cross-linking agents from the system. After the treatment is completed, the system is isolated from air and slowly cooled to room temperature.

[0020] S6 split-mode hot-pressing lamination: Insulating films are laminated to the upper and lower surfaces of the copper substrate, and conductive copper foils are matched to the outer sides of both insulating films. After lamination, the substrate is sent to a vacuum hot press. The hot pressing temperature range is 160-190℃. The pressure is maintained in two stages: the low pressure stage is 0.8-1.2MPa and maintained for 5 minutes for pre-lamination and air removal; the high pressure stage is 1.5-3MPa and maintained for 15-40 minutes. The vacuum degree of the vacuum chamber is ≤0.005MPa to completely remove interlayer air and prevent delamination and bubble defects.

[0021] S7 Segmented Slow Cooling and Shaping: After hot pressing, the mold is not opened immediately. The temperature inside the hot press is slowly reduced to 100°C at a rate of 2°C / min. The semi-finished product is then taken out and allowed to continue to cool slowly in the natural environment for no less than 40 minutes. Water cooling for rapid cooling is prohibited throughout the process. The instantaneous interlayer thermal stress generated by pressing is gradually released. After cooling, a flat finished substrate is obtained directly without the need for additional leveling and calendering processes.

[0022] Optionally, in step S3, the segmented gradient pre-baking uses double-sided hot air circulation heating to ensure uniform heating of the film from top to bottom.

[0023] Optionally, the insulating film treated by the high-temperature vacuum deep devolatilization process in step S5 has no small molecule residue inside, and its dielectric constant and dielectric loss do not drift or fluctuate under long-term high and low temperature conditions, and the millimeter wave signal transmission loss is stable.

[0024] Optionally, the finished product after slow cooling and shaping in step S7 can be directly cut into strips and sent to the etching process to produce high-frequency flexible circuits and millimeter-wave radio frequency antennas. The finished product has no interlayer delamination or delamination after 1000 cycles of bending test.

[0025] Optionally, the hot-pressing composite in step S6 includes two processing forms: single-sided composite and double-sided composite. Single-sided composite only applies insulating film and conductive copper foil to one side of the copper substrate, while double-sided composite involves simultaneously hot-pressing the insulating film and conductive copper foil on both the upper and lower sides of the copper substrate.

[0026] Optionally, in step S4, the constant temperature deep crosslinking is achieved through long-term constant temperature hot air circulation, ensuring that the resin and crosslinking agent react fully, so that the insulating film forms a dense and complete three-dimensional network crosslinking structure, thereby improving the heat resistance and insulation stability of the film.

[0027] Optionally, the entire process of raw material pretreatment and mixing in step S1 is carried out in a closed and light-proof manner to avoid premature decomposition and failure of peroxides, and to ensure that the degree of cross-linking of the film is uniform and consistent, without any defects of insufficient cross-linking in certain areas.

[0028] Optionally, the copper substrate in the prepared metal-based flexible copper-clad foil has a thermal expansion coefficient that is perfectly matched with that of the conductive copper foil, making it suitable for mass production of 5G / 6G high-frequency FPCs, 77GHz automotive millimeter-wave radars, and flexible radio frequency antennas.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] 1. The insulating film of this invention uses a non-polar aliphatic hydrocarbon resin system, which does not contain PI polar materials. Combined with gradient pre-baking, high-temperature cross-linking and long-term vacuum devouring process, small molecule impurities are completely removed. The finished product has Dk≤2.5 and Df≤0.001 in the 5GHz~100GHz frequency band, which greatly reduces the attenuation of millimeter wave signals and is compatible with various high-frequency radio frequency devices, achieving ultra-low high-frequency transmission loss. At the same time, the central copper substrate and the outer conductive copper foil are both made of copper, and their thermal expansion coefficients are completely consistent. After lamination, reflow soldering and high and low temperature cycling, there will be no board warping, line offset, or impedance drift. The dimensional drift of long-term high and low temperature cycling is ≤0.1%, the circuit processing accuracy is significantly improved, and the interlayer thermal stress is completely eliminated.

[0031] 2. The present invention uses a continuous copper substrate as the central support layer of the substrate, which can form a complete electromagnetic shielding structure, effectively suppressing high-frequency signal crosstalk and external electromagnetic radiation interference, improving the signal-to-noise ratio of the radio frequency antenna, without the need for additional shielding film, and achieving self-contained full-area electromagnetic shielding. The flexible hydrocarbon cross-linked film gives the substrate bending performance, which can be used to make flexible FPCs and bendable millimeter-wave antennas. The central copper substrate provides rigid support, and it is not easily deformed during processing and storage. It balances the requirements of flexible processing and high-precision dimensional stability, taking into account both flexibility and dimensional rigidity.

[0032] 3. The price of the hydrocarbon resin raw material of this invention is much lower than that of imported high-frequency PI, LCP and PTFE media. The entire preparation process is controllable and adaptable to continuous mass production. It can replace imported high-end high-frequency substrates, reduce the overall manufacturing cost of high-frequency flexible circuits, make the raw material cost lower and easier to mass produce. The preparation process adopts segmented temperature control, graded hot pressing and slow gradient cooling process. The finished product has high flatness and no additional leveling process is required. After cutting, circuit etching can be carried out directly. The finished product has no delamination or degumming after thousands of repeated bends. It has excellent bending resistance and service life, making the finished product easy to process. Attached Figure Description

[0033] Figure 1 This is a cross-sectional view of the structure of the present invention.

[0034] In the diagram: 1. Copper substrate; 2. Insulating film; 3. Conductive copper foil. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Example 1

[0037] Please see Figure 1 A metal-based flexible copper-clad foil includes a copper substrate 1, with an insulating film 2 bonded to both the top and bottom of the copper substrate 1. A conductive copper foil 3 is bonded to the side of the insulating film 2 away from the copper substrate 1. The insulating film 2 is composed of a nonpolar aliphatic hydrocarbon resin system, forming a three-dimensional network cross-linked structure. By mass, the insulating film 2 is made of 100 parts aliphatic hydrocarbon resin, 0.1 parts peroxide, and 3 parts polyvinyl cross-linking agent. The aliphatic hydrocarbon resin has a nonpolar pure hydrocarbon molecular structure. In the 5GHz-100GHz frequency band, the dielectric constant Dk of the insulating film 2 is ≤2.5, and the dielectric loss Df is ≤0.001. Both the copper substrate 1 and the conductive copper foil 3 are made of copper, and they have the same coefficient of thermal expansion. The copper substrate 1 forms a global electromagnetic shielding structure.

[0038] A method for preparing a metal-based flexible copper-clad laminate, the method comprising the following steps:

[0039] S1 Raw Material Pretreatment and Mixing: Weigh 100 parts aliphatic hydrocarbon resin, 0.1 parts peroxide, and 3 parts polyvinyl crosslinking agent according to the mass ratio. First, put the solid resin into the mixing tank and pre-stir at room temperature for 5 minutes to break up any lumps. Then, add the crosslinking agent in sequence. The stirring speed of the equipment is stably controlled at 300 r / min, and stirring is continued for 20-60 minutes. The stirring process is carried out in a closed and light-proof manner. After stirring, let it stand for 10 minutes to remove bubbles and eliminate air bubbles in the system, so as to obtain a homogeneous coating material without particles. The raw material pretreatment and mixing process is carried out in a closed and light-proof manner to avoid premature decomposition and failure of the peroxide, and to ensure that the degree of crosslinking of the film is uniform and consistent, without local defects of insufficient crosslinking.

[0040] S2 Coating Film Forming: Mirror-finish release PET is selected as the carrier substrate. The defoamed coating material is evenly coated on the surface of the release film using a slot coater. The wet film thickness is controlled at 30μm. The coating environment is kept at a constant temperature of 25℃ and humidity of 40% to avoid rapid evaporation of the wet film, which can cause pinholes and shrinkage defects.

[0041] S3 Segmented Gradient Pre-drying: The release film carrying the wet adhesive film is sent into a segmented hot air oven and dried in two controlled temperature sections. The temperature of the first oven is 140℃ and held for 10 minutes. Low-speed hot air slowly evaporates the low-boiling-point solvent. The temperature of the second oven is raised to 150℃ and held for 15 minutes to further remove residual solvent. The hot air velocity in both ovens is controlled at 0.8m / s to prevent dry skin on the surface of the adhesive film and blistering due to solvent encapsulation inside. The segmented gradient pre-drying uses double-sided hot air circulation heating to ensure uniform heating of the adhesive film from top to bottom.

[0042] S4 Constant Temperature Deep Crosslinking: The pre-baked adhesive film, along with the release film, is transferred to a sealed curing oven. The temperature is raised to 170℃ and held for 40 minutes. Hot air circulates inside the oven, allowing the peroxide to fully decompose and triggering an addition crosslinking reaction between the resin and the polyvinyl crosslinking agent. This results in the formation of a continuous three-dimensional network molecular structure, ensuring a crosslinking reaction conversion rate of ≥95%. The constant temperature deep crosslinking process, through prolonged constant temperature hot air circulation, ensures that the resin and crosslinking agent react fully, enabling the insulating adhesive film 2 to form a dense and complete three-dimensional network crosslinking structure, thus improving the heat resistance and insulation stability of the adhesive film.

[0043] S5 High Temperature Vacuum Deep Deviation: After cross-linking, the release film is peeled off and placed in a vacuum oven. The oven temperature is kept constant at 180℃, and the internal vacuum degree is maintained at ≤0.01MPa. Deviation treatment is carried out for 2 hours. During the process, the vacuum is broken and the air is replaced every 30 minutes to fully extract unreacted monomers, small molecule by-products and residual cross-linking agents from the system. After the treatment, the system is isolated from air and slowly cooled to room temperature. The insulating film 2 after the high temperature vacuum deep deviation process has no small molecule residues inside. Under long-term high and low temperature conditions, the dielectric constant and dielectric loss do not drift or fluctuate, and the millimeter wave signal transmission loss is stable.

[0044] S6 multi-mode hot-press lamination: Insulating film 2 is bonded to both the top and bottom surfaces of copper substrate 1, and conductive copper foil 3 is matched to the outer side of both insulating films 2. After lamination, the substrate is sent to a vacuum hot press. The hot pressing temperature range is 160℃, and the pressure is maintained in two stages. The low pressure stage is 0.8MPa and maintained for 5 minutes for pre-lamination and degassing. The high pressure stage is 1.5MPa and maintained for 15 minutes. The vacuum degree of the vacuum chamber is ≤0.005MPa to completely remove interlayer air and eliminate delamination and bubble defects. Multi-mode hot-press lamination includes two processing forms: single-sided lamination and double-sided lamination. Single-sided lamination only bonds insulating film 2 and conductive copper foil 3 to one side of copper substrate 1. Double-sided lamination simultaneously completes the hot pressing of insulating film 2 and conductive copper foil 3 on both the top and bottom surfaces of copper substrate 1.

[0045] S7 Segmented Slow Cooling and Shaping: After hot pressing, the mold is not opened immediately. The temperature inside the hot press is slowly reduced to 100°C at a rate of 2°C / min. The semi-finished product is then taken out and allowed to continue to cool slowly in a natural environment for no less than 40 minutes. Water cooling is prohibited throughout the process to gradually release the instantaneous interlayer thermal stress generated by pressing. After cooling, a flat finished substrate is obtained directly without additional leveling and rolling processes. The finished product after slow cooling and shaping can be directly cut into strips and sent to the etching process to produce high-frequency flexible circuits and millimeter-wave radio frequency antennas. The finished product has no interlayer delamination or delamination after 1000 cycles of bending test. The thermal expansion coefficients of the copper substrate 1 and the conductive copper foil 3 in the metal-based flexible copper-clad foil are completely matched, making it suitable for mass production of 5G / 6G high-frequency FPCs, 77GHz automotive millimeter-wave radars, and flexible radio frequency antennas.

[0046] The advantages of the above case are: the lowest amount of peroxide and crosslinking agent added, and the lowest raw material cost; the disadvantages are: insufficient crosslinking reaction, low crosslinking density of the film, slight drift of dielectric parameters under high temperature conditions, and it is only suitable for small-batch sample preparation in the laboratory, not for large-scale mass production.

[0047] Example 2

[0048] A metal-based flexible copper-clad foil includes a copper substrate 1. An insulating film 2 is attached to both the top and bottom of the copper substrate 1. A conductive copper foil 3 is attached to the side of the insulating film 2 away from the copper substrate 1. The insulating film 2 is composed of a nonpolar aliphatic hydrocarbon resin system with a three-dimensional network cross-linked structure inside. By mass, the insulating film 2 is made of 100 parts aliphatic hydrocarbon resin, 5 parts peroxide, and 20 parts polyvinyl cross-linking agent. The aliphatic hydrocarbon resin has a nonpolar pure hydrocarbon molecular structure. In the 5GHz-100GHz frequency band, the dielectric constant Dk of the insulating film 2 is ≤2.5 and the dielectric loss Df is ≤0.001. Both the copper substrate 1 and the conductive copper foil 3 are made of copper and have the same coefficient of thermal expansion. The copper substrate 1 forms a global electromagnetic shielding structure.

[0049] A method for preparing a metal-based flexible copper-clad laminate, the method comprising the following steps:

[0050] S1 Raw Material Pretreatment and Mixing: Weigh 100 parts aliphatic hydrocarbon resin, 5 parts peroxide, and 20 parts polyvinyl crosslinking agent according to the following mass ratios. First, add the solid resin to the mixing tank and pre-stir at room temperature for 5 minutes to break up any lumps. Then, add the crosslinking agent sequentially. Maintain a stable stirring speed of 500 r / min and continue stirring for 40 minutes. Keep the mixing process closed and protected from light throughout. After stirring, allow the mixture to stand for 20 minutes to remove air bubbles and obtain a homogeneous, particle-free coating raw material. The entire raw material pretreatment and mixing process is carried out in a closed and light-protected manner to prevent premature decomposition and failure of the peroxide, ensuring uniform crosslinking of the film and eliminating localized defects such as insufficient crosslinking.

[0051] S2 Coating Film Forming: Mirror-finish release PET is selected as the carrier substrate. The degassed coating material is evenly coated on the surface of the release film using a slot coater. The wet film thickness is controlled at 60μm. The coating environment is kept at a constant temperature of 25℃ and humidity of 50% to avoid rapid evaporation of the wet film, which can cause pinholes and shrinkage defects.

[0052] S3 Segmented Gradient Pre-drying: The release film carrying the wet adhesive film is sent into a segmented hot air oven and dried in two sections with controlled temperature. The temperature of the first oven is 140℃ and held for 20 minutes. Low-speed hot air slowly evaporates the low-boiling-point solvent. The temperature of the second oven is raised to 150℃ and held for 20 minutes to further remove residual solvent. The hot air speed of both ovens is controlled at 1m / s to prevent the film surface from drying and the internal solvent from being trapped and bubbling. The segmented gradient pre-drying uses double-sided hot air circulation heating to ensure that the film is heated evenly from top to bottom.

[0053] S4 Constant Temperature Deep Crosslinking: The pre-baked adhesive film, along with the release film, is transferred to a sealed curing oven. The temperature is raised to 170℃ and held for 70 minutes. Hot air circulates inside the oven, allowing the peroxide to fully decompose and triggering an addition crosslinking reaction between the resin and the polyvinyl crosslinking agent. This results in the formation of a continuous three-dimensional network molecular structure, ensuring a crosslinking reaction conversion rate of ≥95%. The constant temperature deep crosslinking process, through prolonged constant temperature hot air circulation, ensures that the resin and crosslinking agent react fully, enabling the insulating adhesive film 2 to form a dense and complete three-dimensional network crosslinking structure, thus improving the heat resistance and insulation stability of the adhesive film.

[0054] S5 High Temperature Vacuum Deep Deviation: After cross-linking, the release film is peeled off and placed in a vacuum oven at a constant temperature of 190℃. The internal vacuum is maintained at ≤0.01MPa for 3.5 hours of continuous devolatilization. During the process, the vacuum is broken and the gas is replaced every 30 minutes to fully extract unreacted monomers, small molecule byproducts and residual cross-linking agents from the system. After the process, the insulation film 2 is cooled to room temperature in the absence of air. After the high temperature vacuum deep devolatilization process, there are no small molecule residues inside the insulation film 2. Under long-term high and low temperature conditions, the dielectric constant and dielectric loss do not drift or fluctuate, and the millimeter wave signal transmission loss is stable.

[0055] S6 multi-mode hot-press lamination: Insulating films 2 are bonded to the top and bottom surfaces of the copper substrate 1 respectively. Conductive copper foils 3 are matched to the outer sides of both insulating films 2. After lamination, the substrate is sent to a vacuum hot press. The hot pressing temperature range is 175℃. The pressure is maintained in two stages: the low pressure stage is 1MPa for 5 minutes for pre-lamination and degassing, and the high pressure stage is 2MPa for 25 minutes. The vacuum degree of the vacuum chamber is ≤0.005MPa to completely remove interlayer air and eliminate delamination and bubble defects. Multi-mode hot-press lamination includes two processing forms: single-sided lamination and double-sided lamination. Single-sided lamination only bonds the insulating film 2 and conductive copper foil 3 to one side of the copper substrate 1. Double-sided lamination simultaneously completes the hot pressing of insulating film 2 and conductive copper foil 3 on both the top and bottom surfaces of the copper substrate 1.

[0056] S7 Segmented Slow Cooling and Shaping: After hot pressing, the mold is not opened immediately. The temperature inside the hot press is slowly reduced to 100°C at a rate of 2°C / min. The semi-finished product is then taken out and allowed to continue to cool slowly in a natural environment for no less than 40 minutes. Water cooling is prohibited throughout the process to gradually release the instantaneous interlayer thermal stress generated by pressing. After cooling, a flat finished substrate is obtained directly without additional leveling and rolling processes. The finished product after slow cooling and shaping can be directly cut into strips and sent to the etching process to produce high-frequency flexible circuits and millimeter-wave radio frequency antennas. The finished product has no interlayer delamination or delamination after 1000 cycles of bending test. The thermal expansion coefficients of the copper substrate 1 and the conductive copper foil 3 in the metal-based flexible copper-clad foil are completely matched, making it suitable for mass production of 5G / 6G high-frequency FPCs, 77GHz automotive millimeter-wave radars, and flexible radio frequency antennas.

[0057] The above-mentioned formulations are balanced: the amount of peroxide and crosslinking agent added is moderate, the crosslinking is sufficient and there is no excessive residue of additives, the film is dense and defect-free, and Dk and Df do not drift significantly under long-term high and low temperatures; the process parameters are moderate: the coating thickness, drying, crosslinking, vacuum, and hot pressing parameters are suitable for continuous production lines, resulting in high production efficiency and stable yield; the overall performance is optimal: the bending performance, shielding effect, dimensional stability, and high-frequency loss all meet the standards, making it suitable for mass industrial production of 5G / 6G and 77GHz radar; the cost is controllable: compared with Example 3, the consumption of additive raw materials is significantly reduced, balancing performance and production costs, making it the optimal solution for the industrialization of this invention.

[0058] Example 3

[0059] A metal-based flexible copper-clad foil includes a copper substrate 1. An insulating film 2 is attached to both the top and bottom of the copper substrate 1. A conductive copper foil 3 is attached to the side of the insulating film 2 away from the copper substrate 1. The insulating film 2 is composed of a nonpolar aliphatic hydrocarbon resin system with a three-dimensional network cross-linked structure inside. By mass, the insulating film 2 is made of 100 parts aliphatic hydrocarbon resin, 2 parts peroxide, and 50 parts polyvinyl cross-linking agent. The aliphatic hydrocarbon resin has a nonpolar pure hydrocarbon molecular structure. In the 5GHz-100GHz frequency band, the dielectric constant Dk of the insulating film 2 is ≤2.5 and the dielectric loss Df is ≤0.001. Both the copper substrate 1 and the conductive copper foil 3 are made of copper and have the same coefficient of thermal expansion. The copper substrate 1 forms a global electromagnetic shielding structure.

[0060] A method for preparing a metal-based flexible copper-clad laminate, the method comprising the following steps:

[0061] S1 Raw Material Pretreatment and Mixing: Weigh 100 parts aliphatic hydrocarbon resin, 2 parts peroxide, and 50 parts polyvinyl crosslinking agent according to the following mass ratios. First, put the solid resin into the mixing tank and pre-stir at room temperature for 5 minutes to break up any lumps. Then, add the crosslinking agent sequentially. The stirring speed of the equipment is kept stable at 800 r / min and stirred continuously for 60 minutes. The stirring process is carried out in a closed and light-proof environment. After stirring, let it stand for 30 minutes to remove bubbles and obtain a homogeneous coating material without particles. The raw material pretreatment and mixing process is carried out in a closed and light-proof environment to avoid premature decomposition and failure of the peroxide, ensuring that the degree of crosslinking of the film is uniform and consistent, without any local defects of insufficient crosslinking.

[0062] S2 Coating Film Forming: Mirror-finish release PET is selected as the carrier substrate. The degassed coating material is evenly coated on the surface of the release film using a slot coater. The wet film thickness is controlled at 120μm. The coating environment is kept at a constant temperature of 25℃ and humidity of 60% to avoid rapid evaporation of the wet film and the generation of pinholes and shrinkage defects.

[0063] S3 Segmented Gradient Pre-drying: The release film carrying the wet adhesive film is sent into a segmented hot air oven and dried in two controlled temperature sections. The temperature of the first oven is 140℃ and held for 25 minutes, with low-speed hot air slowly evaporating the low-boiling-point solvent. The temperature of the second oven is raised to 150℃ and held for 30 minutes to further remove residual solvent. The hot air velocity in both ovens is controlled at 1.5m / s to prevent the film surface from drying and the internal solvent from being trapped and bubbling. The segmented gradient pre-drying uses double-sided hot air circulation heating, ensuring that the film is heated evenly from top to bottom.

[0064] S4 Constant Temperature Deep Crosslinking: The pre-baked film, along with the release film, is transferred to a sealed curing oven and heated to 170℃ for 90 minutes. Hot air circulates inside the oven, allowing the peroxide to fully decompose and triggering an addition crosslinking reaction between the resin and the polyvinyl crosslinking agent, forming a complete continuous three-dimensional network molecular structure. This ensures a crosslinking reaction conversion rate of ≥95%. The constant temperature deep crosslinking process, through prolonged constant temperature hot air circulation, ensures that the resin and crosslinking agent react fully, enabling the insulating film 2 to form a dense and complete three-dimensional network crosslinking structure, thus improving the film's heat resistance and insulation stability.

[0065] S5 High Temperature Vacuum Deep Deviation: After cross-linking, the release film is peeled off and placed in a vacuum oven at a constant temperature of 200℃. The internal vacuum is maintained at ≤0.01MPa for 5 hours of continuous devolatilization treatment. During the process, the vacuum is broken and the gas is replaced every 30 minutes to fully extract unreacted monomers, small molecule byproducts and residual cross-linking agents from the system. After the treatment, the system is isolated from air and slowly cooled to room temperature. The insulating film 2 after the high temperature vacuum deep devolatilization process has no small molecule residues inside. Under long-term high and low temperature conditions, the dielectric constant and dielectric loss do not drift or fluctuate, and the millimeter wave signal transmission loss is stable.

[0066] S6 multi-mode hot-press lamination: Insulating film 2 is bonded to both the top and bottom surfaces of copper substrate 1, and conductive copper foil 3 is matched to the outer side of both insulating films 2. After lamination, the substrate is sent to a vacuum hot press. The hot pressing temperature range is 190℃. The pressure is maintained in two stages: the low pressure stage is 1.2MPa and held for 5 minutes for pre-lamination and degassing, and the high pressure stage is 3MPa and held for 40 minutes. The vacuum degree of the vacuum chamber is ≤0.005MPa to completely remove interlayer air and eliminate delamination and bubble defects. Multi-mode hot-press lamination includes two processing forms: single-sided lamination and double-sided lamination. Single-sided lamination only bonds insulating film 2 and conductive copper foil 3 to one side of copper substrate 1. Double-sided lamination simultaneously completes the hot pressing of insulating film 2 and conductive copper foil 3 on both the top and bottom surfaces of copper substrate 1.

[0067] S7 Segmented Slow Cooling and Shaping: After hot pressing, the mold is not opened immediately. The temperature inside the hot press is slowly reduced to 100°C at a rate of 2°C / min. The semi-finished product is then taken out and allowed to continue to cool slowly in a natural environment for no less than 40 minutes. Water cooling is prohibited throughout the process to gradually release the instantaneous interlayer thermal stress generated by pressing. After cooling, a flat finished substrate is obtained directly without additional leveling and rolling processes. The finished product after slow cooling and shaping can be directly cut into strips and sent to the etching process to produce high-frequency flexible circuits and millimeter-wave radio frequency antennas. The finished product has no interlayer delamination or delamination after 1000 cycles of bending test. The thermal expansion coefficients of the copper substrate 1 and the conductive copper foil 3 in the metal-based flexible copper-clad foil are completely matched, making it suitable for mass production of 5G / 6G high-frequency FPCs, 77GHz automotive millimeter-wave radars, and flexible radio frequency antennas.

[0068] The advantages of the above cases are: the highest addition of crosslinking agents and initiators, extremely high crosslinking density, and the strongest dielectric stability in extreme high and low temperature environments, making them suitable for military-grade millimeter-wave special devices; the disadvantages are: large amount of additives, significantly increasing raw material costs; longer drying, crosslinking, vacuuming, and hot pressing processes, low production line efficiency, low cost-effectiveness for mass production of ordinary consumer electronics and automotive radar, and only suitable for special high-end scenarios.

[0069] Of the three embodiments described above, Embodiment 2 is the optimal embodiment of the present invention. The formula and process parameters are balanced, and the overall dielectric, bending, dimensional stability, production cost and mass production yield are all optimally balanced, making it suitable for most 5G / 6G and automotive millimeter-wave radar mass production scenarios.

[0070] In actual production, the corresponding composite processing method can be selected according to the wiring requirements of the terminal product. Single-sided wiring products only perform single-sided hot-pressing composite process, while double-sided wiring products use double-sided hot-pressing composite. Other raw material ratios and heat treatment process parameters do not need to be adjusted.

[0071] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A metal-based flexible copper-clad foil, characterized in that: The copper substrate (1) is covered with an insulating film (2) on both the top and bottom of the copper substrate (1). A conductive copper foil (3) is attached to the side of the insulating film (2) away from the copper substrate (1). Both the copper substrate (1) and the conductive copper foil (3) are made of copper and have the same coefficient of thermal expansion. The copper substrate (1) forms a full-area electromagnetic shielding structure. The insulating film (2) is composed of a nonpolar aliphatic hydrocarbon resin system, and has a three-dimensional network cross-linked structure inside. By mass, the insulating film (2) is made of 100 parts aliphatic hydrocarbon resin, 0.1-20 parts peroxide and 3-50 parts polyvinyl cross-linking agent. The aliphatic hydrocarbon resin has a nonpolar pure hydrocarbon molecular structure.

2. The metal-based flexible copper-clad foil according to claim 1, characterized in that: In the 5GHz-100GHz frequency band, the dielectric constant Dk of the insulating film (2) is ≤2.5 and the dielectric loss Df is ≤0.

001.

3. A method for preparing a metal-based flexible copper-clad foil, characterized in that: The preparation method used for the metal-based flexible copper-clad foil according to any one of claims 1-2 specifically includes the following steps: S1 Raw Material Pretreatment and Mixing: Weigh 100 parts aliphatic hydrocarbon resin, 0.1-20 parts peroxide and 3-50 parts polyvinyl crosslinking agent according to the mass ratio. First, put the solid resin into the mixing tank and pre-stir at room temperature for 5 minutes to break up the lumps. Then, add the crosslinking agent in sequence. The stirring speed is stably controlled at 300-800 r / min. Stir continuously for 20-60 minutes. The stirring process is completely sealed and protected from light. After stirring, let it stand for 10-30 minutes to remove bubbles and obtain a homogeneous coating raw material without particles. S2 Coating Film Forming: Mirror release PET is selected as the carrier substrate. The degassed coating material is evenly coated on the surface of the release film using a slit coater. The wet film thickness is controlled at 30-120μm. The coating environment is kept at a constant temperature of 25℃ and humidity of 40%-60% to avoid rapid evaporation of the wet film and the generation of pinholes and shrinkage defects. S3 Segmented Gradient Pre-drying: The release film carrying the wet adhesive film is sent into a segmented hot air oven and dried in two sections with controlled temperature. The temperature of the first oven is 140℃ and held for 10-25 minutes. Low-speed hot air slowly evaporates the low-boiling-point solvent. The temperature of the second oven is raised to 150℃ and held for 15-30 minutes to further remove residual solvent. The hot air velocity in both ovens is controlled at 0.8-1.5m / s to prevent the film surface from drying and the internal solvent from being trapped and bubbling. S4 Constant Temperature Deep Crosslinking: The pre-baked film, along with the release film, is transferred into a sealed curing oven. The entire oven is heated to 170℃ and kept at that temperature for 40-90 minutes. Hot air is circulated inside the oven to fully decompose the peroxides and initiate an addition crosslinking reaction between the resin and the polyvinyl crosslinking agent, forming a complete continuous three-dimensional network molecular structure. This ensures a crosslinking reaction conversion rate of ≥95%. S5 High Temperature Vacuum Deep Deviation: After cross-linking, the release film is peeled off and placed in a vacuum oven. The oven temperature is kept constant at 180-200℃, and the internal vacuum degree is maintained at ≤0.01MPa. Deviation treatment is carried out for 2-5 hours. During the process, the vacuum is broken and the air is replaced every 30 minutes to fully extract unreacted monomers, small molecule by-products and residual cross-linking agents from the system. After the treatment is completed, the system is isolated from air and slowly cooled to room temperature. S6 mode hot pressing composite: Insulating film (2) is bonded to the upper and lower sides of the copper substrate (1) respectively. Conductive copper foil (3) is matched on the outer side of both insulating films (2). After the composite is completed, it is sent into a vacuum hot press. The hot pressing temperature range is 160-190℃. The pressure is maintained in two stages. The low pressure stage is 0.8-1.2MPa and maintained for 5 minutes for pre-bonding and degassing. The high pressure stage is 1.5-3MPa and maintained for 15-40 minutes. The vacuum degree of the vacuum chamber is ≤0.005MPa to completely remove interlayer air and eliminate delamination and bubble defects. S7 Segmented Slow Cooling and Shaping: After hot pressing, the mold is not opened immediately. The temperature inside the hot press is slowly reduced to 100°C at a rate of 2°C / min. The semi-finished product is then taken out and allowed to continue to cool slowly in the natural environment for no less than 40 minutes. Water cooling for rapid cooling is prohibited throughout the process. The instantaneous interlayer thermal stress generated by pressing is gradually released. After cooling, a flat finished substrate is obtained directly without the need for additional leveling and calendering processes.

4. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: In step S3, the segmented gradient pre-baking uses double-sided hot air circulation heating to ensure uniform heating of the film from top to bottom.

5. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: The insulating film (2) after the high temperature vacuum deep devolatilization process in step S5 has no small molecule residue inside, and the dielectric constant and dielectric loss do not drift or fluctuate under long-term high and low temperature conditions, and the millimeter wave signal transmission loss is stable.

6. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: The finished product after slow cooling and shaping in step S7 can be directly cut into strips and sent to the etching process to make high-frequency flexible circuits and millimeter-wave radio frequency antennas. The finished product has no interlayer delamination or delamination after 1000 cycles of bending test.

7. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: In step S6, the hot-pressing composite process includes two processing methods: single-sided composite and double-sided composite. In single-sided composite, the insulating film (2) and the conductive copper foil (3) are bonded to only one side of the copper substrate (1). In double-sided composite, the insulating film (2) and the conductive copper foil (3) are simultaneously bonded and hot-pressed on both the upper and lower sides of the copper substrate (1).

8. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: In step S4, constant temperature deep crosslinking is achieved through long-term constant temperature hot air circulation, which ensures that the resin and crosslinking agent react fully, so that the insulating film (2) forms a dense and complete three-dimensional network crosslinking structure, thereby improving the heat resistance and insulation stability of the film.

9. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: In step S1, the entire process of raw material pretreatment and mixing is carried out in a closed and light-proof manner to prevent the peroxide from decomposing and failing prematurely, and to ensure that the cross-linking degree of the film is uniform and consistent, without any defects of insufficient cross-linking in certain areas.

10. The method for preparing metal-based flexible copper-clad foil according to claim 3, characterized in that: The copper substrate (1) in the prepared metal-based flexible copper-clad foil has a thermal expansion coefficient that is perfectly matched with that of the conductive copper foil (3), making it suitable for mass production of 5G / 6G high-frequency FPC, 77GHz vehicle-mounted millimeter-wave radar and flexible radio frequency antenna.